Shifting paradigms in the study of personality: a retrospective survey of western ideas - Abdul Razak, Mohd Abbas; Ismail, Nik Ahmad Hisham (IIUM Press, 2014)
The birth of the Renaissance movement in the West ushered the scholars as well as the masses into a broader perspective of learning and knowledge seeking. The spirit of the Renaissance paved the way forward for scholars to gain freedom of speech and liberation from their old mindset. Europe that was bursting with new philosophical and scientific ideas also gave its people a wide range of perspectives in understanding man and personality. Secularism and modernism that came as a result of the Renaissance movement caused a shift in the understanding on man and his personality from a religious to a scientific one. In this study, the researchers would like to venture into the areas of man and personality from the Western perspective. Very precisely, the researchers would like to conduct a survey on the shifting paradigms in the field of Western psychology, pertaining to the study on man and personality. Upon performing the survey, the researchers would like to identify and analyze the underlying factors that caused the emergence of the different paradigms in Western psychology